STRUCTURE-ACTIVITY-RELATIONSHIP OF THE POLYPHENOLS INHIBITION OF α-AMYLASE AND α-GLUCOSIDASE - Bamigboye, Taiwo Josiah; Olubiyi, Olujide Oludayo; Olawuni, Idowu J.; Van Heerden, Fanie R. (African Journal of Traditional, Complementary and Alternative Medicines, 2023)
Background: Diabetes mellitus (DM) is a serious public health challenge, projected by WHO to be one of the 7 leading cause of death by 2030. Medicinal plants have been demonstrated to be useful in DM local management because of polyphenols present in these plants. For an alternative treatment approach especially with polyphenols-rich herbs, knowledge of comparative efficacy of the polyphenols will lead to enhanced therapy especially in postprandial hyperglyceamic control. Materials and Methods:Vegetative parts of Anacardium occidentale, Abelmoschus ecsulentus and Ceiba pentandra, prominent in the local management of DM were identified, collected and subjected to alcoholic extraction. From the crude extracts were isolated agathisflavone, quercetin 3-O-glucoside, quercetin 3-O-diglycoside, mangiferin, isomangiferin and pentagalloyl glucose, belonging to flavonoid, xanthones and tannins structural classes. These polyphenols were evaluated for their potentials to inhibit both α-glucosidase and α-amylase. Physicochemical parameters of the polyphenols were evaluated and molecular docking experiments were carried out to gain insight into the observed inhibitory activity. Results: quercetin 3-O-glucosidewas the most potent of the polyphenols against the two enzymes. Increase in the number of phenolic hydroxyl group did not increase the inhibitory activity and neither computation of the binding energies with the enzymes nor physicochemical parameters of the polyphenols could explain the observed inhibitory activity against the enzymes, across the structural classes. Thus, only the bioassay against the enzymes α-glucosidase and α-amylase correlated well with the use of the plants in treating diabetic mellitus Conclusion: Medicinal plants rich in quercetin 3-O-glycoside may have better treatment outcomes in postprandial hyperglycaemia control.